Desafios dos professores para mediação pedagógica de estudantes com transtorno do espectro autista na educação profissional e tecnológica - Garcia, Tainan Silva (2024)
The work entitled “Teachers' Challenges for Pedagogical Mediation of Students with Autism Spectrum Disorder (ASD) in Vocational and Technological Education (EPT)” is part of the research line Teacher Training for Vocational and Technological Education. The research was developed based on the question: what are the training needs of teachers to mediate learning? In this context, the present work aims to analyze the challenges faced by teachers in pedagogical mediation of students with ASD in EPT to propose a continuing training course. The research is structured into 3 manuscripts, where the first study consists of a case study, from an exploratory perspective. The second manuscript aims to identify whether teachers use technology resources to mediate learning and how they use them. The research is a field study with a qualitative and quantitative approach, with an exploratoryexplanatory nature. The third manuscript is anchored in the Design BasedResearch (DBR) methodology, aiming to plan a teacher training course that could contribute to minimizing the perceived difficulties, both in the literature analyzed and in the data returned from the survey. To better understand the real context of the research, a literature review was initially carried out, to understand what has been researched about this, in this research section. Furthermore, a survey-type questionnaire was used as a data collection instrument. The research subjects were 31 teachers working in Vocational and Technological Education. The quantitative data collected in the research was analyzed using descriptive statistics, and the qualitative data analyzed based on Bardin's Content Analysis. The results indicate that there is a gap in the literature in relation to the teaching and learning processes of people with autism spectrum disorders in EPT, which, in itself, already justifies this work. The data returned from the survey allows us to infer that, although some teachers have knowledge about what ASD is, for many, the knowledge is superficial and they do not feel prepared for pedagogical mediation for these subjects. Thus, at the end of this work, a design principle for a teacher training course focused on ASD is outlined.